Filsafat Pendidikan Islam: Integrasi Nilai-Nilai Spiritual dalam Sistem Pendidikan Modern - Basori Basori; Mifta Yuljannah Pasaribu; Reva Nur Amalya (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Modern education often emphasizes cognitive and technological aspects, while spiritual aspects are often neglected. In fact, in Islamic educational philosophy, the integration of spiritual values ​​is an important part in forming the character of students who are moral and competitive. This study aims to (1) analyze the concept of Islamic educational philosophy from the perspective of integrating spiritual values, (2) identify spiritual values ​​that can be integrated into the modern education system, and (3) explore effective strategies in their implementation. The method used is a literature review with a descriptive-analytical approach to relevant sources. The results of the study indicate that Islamic educational philosophy emphasizes a balance between intellectual and spiritual aspects to form individuals who have high moral awareness. Spiritual values ​​such as monotheism, morals, and worship can be adapted into a modern curriculum through contextual and experience-based learning methods. The implementation of this integration strategy includes a holistic approach in the curriculum, teacher training, and the creation of a learning environment that supports the spiritual growth of students. Thus, the integration of spiritual values ​​in modern education contributes to the formation of a more complete and balanced character.